KAT II: Tactile display mouse for providing tactile and thermal feedback - Yang, Gi-Hun; Kwon, Dong-Soo (TAYLOR & FRANCIS LTD, 2008)
This paper proposes a tactile display mouse providing both pin-array-type tactile feedback and thermal feedback. The pin-array-type tactile display is composed of a 6 x 5 pin-array that is actuated by 30 piezoelectric bimorphs. Micro shape and vibrotactile feedback can be generated by the device, and various planar distributed patterns can be displayed as can Braille cell patterns. The thermal feedback device is composed of a thin-film resistance temperature detector, a Peltier thermoelectric heat pump and a water cooling jacket. Users can discriminate among different materials by considering the temperature variation that can be sensed as they touch an object's surface. This paper also includes an experimental evaluation of the tactile display mouse to prove the effectiveness of displaying textures. Evaluation of the ability to identify material properties was conducted using the thermal feedback part that displays a simulated temperature profile. To investigate thermo-tactile interaction, an experiment determining perceived magnitude of vibrotactile stimulus according to different temperature conditions was conducted. (c) Koninklijke Brill NV, Leiden and The Robotics Society of Japan, 2008
Keywords: SKIN TEMPERATURE